(untitled) (SCIENCE TIME JOURNAL, 2026)
. This article examines lexical transformations in the translation of English newspaper and publicistic texts into Uzbek. The study analyzes linguistic, stylistic, and cultural challenges that emerge during the transfer of meaning from English into Uzbek newspaper discourse. English journalism frequently employs compressed syntax, metaphorical headlines, idiomatic expressions, and culture-specific references, whereas Uzbek publicistic discourse prioritizes clarity, accessibility, and explanatory structures. Using examples from British newspapers, particularly Brexit-related headlines, the study demonstrates how translators apply lexical transformations such as expansion, adaptation, reformulation, and contextual substitution. The findings reveal that successful newspaper translation requires preserving not only semantic meaning but also stylistic function, emotional effect, ideological orientation, and communicative impact. The article concludes that lexical transformations are essential tools for achieving equivalence between English and Uzbek newspaper discourse while adapting journalistic texts to the linguistic and cultural norms of the Uzbek language.